The Development of Continuing Nursing Model in Pemphigus Patients at the Institute of Dermatology - Chantavoraluk, Somjai; Sripoka, Inglada; Yimwadsana, Pantip; Pakeenet, Chintana; Lekhavat, Chinmanat (Journal of The Department of Medical Services, 2021)
Background : Pemphigus is a chronic autoimmune blistering skin disease. The severity degree of the disease can be varied, affecting the quality of life and even death from its complications such as infections, and the use of immunosuppressants. Patients need to receive continued care from hospital to home to avoid possible complications. Objective : To develop and study the results of a continuing nursing model in pemphigus patients. Methods : This was a research and development study. The data were collected on 17 professional nurses and 68 patients (8 patients with moderate disease severity or worse and 60 patients with mild diseases severity) at the Institute of Dermatology. We analyzed the problems and developed a nursing model for continuing care in pemphigus patients. The data were analyzed through content analysis. Wilcoxon signed-rank test and Paired t-test were used to compare the differences between pre and post processing of the continuing nursing model. Results : The nursing model for continuing care of pemphigus diseases was developed to address 1) Nursing practice guideline 2) Discharge planning program 3) Health education plan 4) Pemphigus Patient’s identification book 5) Assigning nurses to monitor patients at home by phone 6) Exchanging information about patient problems between the inpatient ward and the vesiculobullous clinic. The professional nurses had a statistically higher knowledge than before implementing the model (p<0.05). Mean nurses’ operation following the nurse care model was 86.42%, and nurse satisfaction was at the highest level. The patients with all disease severity levels had significantly higher mean score of self-care knowledge (p<0.05). Patients with mild disease severity had a significantly higher mean score in care behavior (p<0.05) although there was no statistically significant difference between before and after model in patients with moderate and more disease severity (p>0.05). Patient satisfaction was at the highest level in all severity group after the model was used. The re-visit rates reduced from 5.96% to 1.67% in the mild disease severity group, while the readmission rates reduced from 4.33% to 0% in the moderate and more disease severity group. Conclusion : The development of continuity nursing model in pemphigus could support the professional nurses’ practice in continuing care. Educated patients were able to take care of themselves, resulting in a significant reduction in complications and the revisit and readmission rates.